2016
DOI: 10.1016/j.joca.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Importance of reference gene selection for articular cartilage mechanobiology studies

Abstract: SummaryObjectiveIdentification of genes differentially expressed in mechano-biological pathways in articular cartilage provides insight into the molecular mechanisms behind initiation and/or progression of osteoarthritis (OA). Quantitative PCR (qPCR) is commonly used to measure gene expression, and is reliant on the use of reference genes for normalisation. Appropriate validation of reference gene stability is imperative for accurate data analysis and interpretation. This study determined in vitro reference ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Real-time PCR was performed using a MxPro3000 QPCR system (Agilent Technologies, Stockport, UK) using ReadyMix™ Taq PCR reaction mix in conjunction with a Taqman® gene expression assay (Hpn: Bt03260765_m1; ThermoFisher Scientific (Loughborough, UK)). 18 S was used as a reference gene as previously described 46 .…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was performed using a MxPro3000 QPCR system (Agilent Technologies, Stockport, UK) using ReadyMix™ Taq PCR reaction mix in conjunction with a Taqman® gene expression assay (Hpn: Bt03260765_m1; ThermoFisher Scientific (Loughborough, UK)). 18 S was used as a reference gene as previously described 46 .…”
Section: Methodsmentioning
confidence: 99%
“…The wrong choice of reference gene for the normalization of RT-qPCR data may give rise to wildly inaccurate results [ 4 ]. For example, hypoxanthine phosphoribosyltransferase (HPRT) was demonstrated to be a suitable reference gene in placental tissues from intrahepatic cholestasis of pregnancy [ 5 ] and in bladder cancer cells [ 6 ], while it was found to be unsuitable for articular cartilage [ 7 ]. GAPDH and β-actin, which are the most commonly used reference genes in molecular biological studies, have been demonstrated to be useful reference genes in human prostate cancer [ 8 ], while they have been found to be unsuitable for normalizing mRNA levels in human asthmatic airways [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative polymerase chain reaction (qPCR) was performed using SYBR green detection (Brilliant III Ultra‐Fast SYBR® QPCR mix, Agilent Technologies) using intron‐spanning primers for genes of interest (Suppl. Table S3), on a QPCR machine (MxPro3000, Agilent Technologies). All reactions were carried out at an annealing temperature of 60°C unless specified otherwise (Suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Primers (MWG‐Biotech AG, Germany), were used at a final concentration of 200 nM and validated using cDNA standard curves with all primer efficiencies between 90 and 110% . Data were normalized to 18s and β‐actin which were identified from 8 reference genes using RefFinder (http://150.216.56.64/referencegene.php) as maintaining stable expression under these experimental conditions . Fold‐change in expression of genes of interest was calculated using the 2 −ΔΔCT method, after normalization to the reference genes and presented relative to the uninjured contra‐lateral limb.…”
Section: Methodsmentioning
confidence: 99%